THE ROLE OF MIGRANT WORKERS IN IMPROVING FAMILY WELFARE THROUGH THE PERSPECTIVE OF ISLAMIC ECONOMIC LAW: Study in Panggungrejo Gondanglegi Malang - Syarofi, Ahmad Muhtar (LP3M IAI Al-Qolam, 2024)
This research aims to answer the question about the understandings of Islamic economic law on the role of migrant worker women in improving family economic welfare. This research uses a qualitative descriptive approach. The primary data sources of this study are interviews, observations, interviews, and documents analysis. the theory has been adjusted in this study, namely, (the role of female workers in the welfare of the family economy) Participation of overseas female workers has an important role in improving the welfare of the family as a whole. They can buy the various daily necessities, have a private vehicle , build houses, and buy land. Their lives are included in the prosperous category, which differentiates them from their previous lives and other societies. Meanwhile, in the perspective of Islamic Economic Law, the participation of migrant worker women played an important role in improving people's welfare. Based on the research results, their participation is in accordance with Islamic principles. The fulfillment of this welfare are based on the indicators described in the Al-Qur'an. The income earned by women as migrant workers can help them meet basic needs such as adequate consumption, as well as creating a sense of comfort, security and peace.